International legal issues of social security in the period of world financial and economic crisis - Postovalova, Tatjana A. (Journal of the Belarusian State University. Law, 2019)
Despite the fact that the need for social protection is recognized throughout the world, the fundamental human right to social security remains unrealized for a large part of the world’s population. The purpose of this article is a comprehensive analysis of the nature and trends of development of international legal problems of social security in the period of the world financial and economic crisis and the definition of the main approaches to their resolution, as well as the study of international legal acts and soft law on social security issues and the formation of proposals on the improvement of international legal principles and norms. The subject of this article is international legal relations in the field of social security in the period of world financial and economic crisis. In the article it have been developed a number of theoretical provisions and practical recommendations, in particular, new trends in the improvement of the international legal framework for social security during the world financial and economic crisis have been revealed, the features of regulation of social security in the context of international law, the legal evaluation of proposals on ways to improve social security during the period of world financial and economic crisis. The main provisions and conclusions can be used as a doctrinal source in the process of forming the position of the Republic of Belarus in the preparation of international legal instruments and their implementation, in discussing the problems of social security of international organizations, as well as in educational activities in the preparation and reading of training courses on social security law, international law, as well as social and medical law.